(untitled) (Research, Society and Development, 2021)
Dairy foods represent a large market, grossing more than 125 billion per year worldwide. Dairy effluent has high organic load and therefore must be treated before disposing in the water bodies. Natural coagulants represent a good option for effluent treatment, among which is the Moringa Oleífera (MO) seed. In this sense, the present work experimentally evaluates the effluent treatment efficiency of the dairy industrial effluents using coagulants based on the MO seed, also discussing environmental and economic potentialities of seed planting. Evaluation was carried out by use of the MO seed both directly (comminuted) and in saline solution by Jar Test essay. The COD clarification and removal efficiency of the crude sample was evaluated for different initial turbidity and coagulant volume scenarios. The results showed a high turbidity reduction efficiency (between 97 and 99%) in most of the tests by the direct use of MO seeds. The cropped area required for this application in a dairy industry with processing of 10 m³ of milk per day was 1775 m². The use of MO seed in saline solution did not achieve the same efficiency, indicating the need to optimize the test parameters. The results might to base more extensive discussions of potentialities and limitations of the use of MO seed as a potential coagulant.